KONTRIBUSI PARAMETER METEOROLOGI DAN KONDISI LALU LINTAS TERHADAP KONSENTRASI PENCEMAR NO2 DI KOTA SEMARANG - Istirokhatun, Titik; Ratnasari, Elaeis Noviani; Utomo, Sudarno (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2016)
Air pollution and its public health effects are drawing increasing concern from the environmental health research community, environmental regulatory agencies, industries as well as public. Nitrogen dioxide (NO2) is one of those common air pollutants that potentially major cause health problems. Transportation contributed most of the air pollution. In addition, the number of vehicles that are passing and queuing on the crossroads because of traffic light can affect the concentration of NO 2. Besides, in these places there are a lot of road users which are potentially exposed by contaminants, so information about the concentration of NO2 on road side is important to know. This study aimed to investigate the impact of meteorological factors and the number of vehicles on NO2 concentrations. Impinger fritted bubler was used for air sampling, and Griess Saltzman method was used for determining NO2 concentration. Sampling and calculation of the number of passing vehicles were performed 3 times ie in the morning, afternoon and evening. Based on the results of the study, the highest concentrations of NO2 were on the range of 0.7-4.2 mg/Nm3.